Scoping paper on industry in Senegal - Fatou Cissé; Ji Eun Choi; Mathilde Maurel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Senegal is a typical sub-Saharan economy, which conducted an import substitution policy over 1960-86, followed by a policy of support for the private sector and liberalization of the economy. It suffers from a low level of economic development, hindering the process of economic diversification, and translating into an over-concentration of its exports and production. Through a careful analysis of the main advantages and drawbacks of the Senegalese economy, this scoping paper emphasizes the key obstacles to unleashing prosperity in the country: electricity supply and quality, and the educational system.
Keywords: O55; 330; export and production concentration; industrial policies; key obstacles to growth